Synthesis of molecularly printed methyl methacrylate-based polymers for the detection of di(2-ethylhexyl) phthalate and dibutyl phthalate - Fauziah, St.; Soekamto, Nunuk Hariani; Prastawa, Budi; Rasyid, Herlina; Haedar, Nur; Hustim, Muralia; Marlina, Marlina; Sulaiman, Magfirah; Sapar, Ajuk (Polimery, 2023)
Molecularly imprinted polymers (MIP) were obtained by precipitation polymerization for the detection of DEHP and DBP from polymer packaging in drinking water. MIP was obtained by cross-linking DEHP and DBP with methyl methacrylate (MMA) and trimethylolpropane trimethacrylate (TRIM). FTIR, SEM-EDS, UV-Vis and SAA were used to determine properties of polymers (MIP_DEHP, MIP_DBP). The obtained materials were characterized by a mesoporous structure with small, uniform, and porous grains. The surface area and total pore volume of MIP_DEHP were more than twice smaller than MIP_DBP, with a slightly larger pore diameter. Lower C content may indicate the formation of MIP_DEHP and MIP_DBP. The FTIR method confirmed the presence of functional groups –CH, –CO, –C=C and –C=O. The adsorption capacity of MIP_DEHP and MIP_DBP was 0.68 mg/g and 1.06 mg/g, respectively, and was consistent with the Freundlich isothermal adsorption model.